568 XTX201, a protein-engineered IL-2, exhibits tumor-selective activity in mice without peripheral toxicities in non-human primates. (9th November 2020) - Zhang, Minjie; Guzman, Wilson; Johnson, Parker; McLaughlin, Megan; Jenkins, Kurt; Wu, Hsin-Jung; Madala, Hanumantha Rao; O'Toole, Caitlin; Pederzoli-Ribeil, Magali; Rozenfeld, Raphael; Qiu, Huawei; Karow, Margaret; et al.
Abstract : Background: High-dose recombinant human interleukin-2 (aldesleukin) elicits durable anti-tumor immunity and gained FDA approval two decades prior to checkpoint blockers. However, use of aldesleukin is limited due to treatment-related life-threatening toxicities. Second generation efforts to alleviate toxicities have largely focused on eliminating binding to IL-2Rα, often with half-life extension. We have determined that mice and non-human primates (NHPs) treated with a 2nd generation IL-2 surrogate that does not bind IL-2Rα still experience characteristic dose-limiting toxicities, including vascular leak syndrome (VLS), and exhibit dysregulated peripheral immune function due to reduced Treg activation. To overcome these toxicities and improve the therapeutic index of IL-2 as an anti-tumor immunotherapy, we employed protein engineering to generate XTX201, a highly potent 3rd generation IL-2 that is designed to be selectively active in tumors, stimulating cytolytic responses against tumor cells while sparing systemic immune activation. Methods: XTX201 binding interactions were measured with SPR, and bioactivity was measured using STAT-5 phosphorylation in human PBMCs and reporter cell lines. Anti-tumor efficacy and immune activation was evaluated in tumors compared to peripheral organs in syngeneic tumor mouse models. Safety and pharmacokinetics were evaluated in rodents and NHPs. Results: Non-activated XTX201 showed no detectable binding to IL-2Rα or IL-2Rβ, and limited IL-2R-dependent STAT-5 signaling in vitro. Activation of XTX201 resulted in high-affinity binding to IL-2Rβ and no binding to IL-2Rα, leading to a ~1000-fold reduction in Treg activation as compared to WT IL-2, while retaining CD8+ T and NK cell activation. Mice and NHPs treated with a 2nd generation IL-2 surrogate experienced toxicities that are commonly observed in patients treated with aldesleukin, including pulmonary edema, VLS, fever and lethality. However, XTX201 did not induce toxicities at exposures 100-fold higher than the MTD of the activated version, and achieved similar anti-tumor efficacy in mice. Experiments in primary human solid tumors and human plasma indicated that XTX201 is preferentially activated in the tumor microenvironment. Conclusions: Our data demonstrate that 2nd generation IL-2s that are systemically active and lack binding to IL-2Rα exhibit dose-limiting toxicities unless further engineered for selective activity in tumors. XTX201, a 3rd generation, tumor-selective IL-2, exhibits a long half-life and is innocuous outside of tumors. XTX201 is activated within tumors to release an IL-2Rβ/γ biased cytokine that inhibits tumor growth in syngeneic models, and exhibits tumor-specific pharmacodynamic effects without peripheral toxicities. XTX201 has the potential to be a best-in-class IL-2 immunotherapy by expanding the curative anti-tumor activity of aldesleukin while minimizing dose-limiting toxicities.